A Review on the Diagnosis and Management of Bites in the Canon of Medicine of Avicenna - Jamal Rezaei--Orimi; Ebrahim Nasiri; Mostafa Moallemi; Sohrab Padashi (Journal of Mazandaran University of Medical Sciences, 2019)
Background and purpose: Bites of animals and poisonous insects cause high mortality and morbidity rates in the world, therefore, prevention and appropriate treatment are of great importance. This study was carried out to investigate the diagnosis and treatment of bites of animals and poisonous insects on the basis of the Canon of Medicine of Avicenna. Materials and methods: The Canon of Medicine of Avicenna was reviewed using the following keywords: bite, sting, animals, and poisonous insects. Texts related to the diagnosis and treatment of bites and stings of various animals and poisonous insects were extracted and analyzed. Results: Diagnostic methods for bites included careful examination of the patient, signs and symptoms of bites, classification of animals and poisonous insects, such as snakes, bees, tarantula, etc. Treatment methods were mainly based on no penetration of poison based on natural drugs and external absorbing agents (non-medical treatments). There were also more than 180 herbal, animal, and mineral compounds, and compound drugs in the treatment of bites. Conclusion: In the Canon of Medicine of Avicenna, several methods are introduced for diagnosis and treatment of bites of animals and poisonous insects which are extremely similar to current methods. But, further studies are required with more scientific evidences on other materia.